THE GEOPOLITICAL POSITION OF THE TURKIC WORLD AND THE GEOGRAPHY OF TRANSPORT AND ECONOMIC RELATIONSHIPS - Imrani Zaur Tahir,; Musayeva Matanat Ramazan,; Orucov Polad Shamistan, (Scientific Journal of Pedagogy and Economics, 2021)
Notwithstanding the fact that our planet is characterized by scientific, technical, political and economic achievements from the beginning of the XXI century, there is still problems in development, socioeconomic backwardness, and problems in the management and determination of borders between countries. The Turkic states, which recently gained independence, are trying to determine their geopolitical position in the political arena of the world, which is mainly associated with the development of their transport and economic relationhips. The favorable geostrategic position of the Turkic world countries, their location at the crossing of various transport corridors accelerated their integration into the world economic system. Therefore, the valuation of the capabilities of the Turkic states in the modern world is of great relevance. This paper uses historical, statistical, comparative, analysis method, systematic and other methods. Using these methods was carried out a geographical analysis of the geopolitical situation and the transport and economic relations of the Turkic world. Economic development, mutual cooperation, positive demographic dynamics and other processes in the modern world are among the interests of the Turkic world. Because the geopolitical situation in the Turkic world and its ability to influence international political situation serve the interests of the region as a whole.